The bride wore pearls ebook - Carlyle, Liz (Fraternitas Aureae Crucis, 2023)
"[Carlyle's] final Fraternitas romance paints Victorian society with sensual undertones . . . suspense and romance entwine to create an engaging read." — Publishers Weekly Beneath the elegant façade of Victorian high society, the rules of danger and desire are the only rules that apply for the mysterious men of the St. James Society.  New York Times –bestseller Liz Carlyle carries readers deep into this realm of intrigue and passion once more in her breathtaking historical romance sizzler,  The Bride Wore Pearls . The third book in her sexy, compelling, action-packed series,  The Bride Wore Pearls  is a scorching story of a very proper lady who flees her home in a far corner of the British Empire, entrusting her safety and her heart to a dangerous outlaw in Victorian London. Amanda Quick and Gaelen Foley fans will most certainly be enthralled. Praise for the Fraternitas Aureae Crucis series "Intriguing . . . engaging . . . an illicit delight." —Stephanie Laurens, #1 New York Times –bestselling author "Liz Carlyle weaves passion and intrigue with a master's touch." —Karen Robards, New York Times –bestselling author